The Empowering Pregnant Women through Prenatal Yoga Assistance - Maya Hapsari Hijramastia; Septiana Juwita; Niken Bayu Argaheni (UNUSA Press, 2023)
Pregnancy causes physical and psychological changes, so the body needs adaptations that interfere with the mother's metabolism. The adaptation stage will cause discomfort in pregnancy and childbirth later. Ten of the third-trimester pregnant stated that they were worried about themselves and the fetus they were carrying. The purpose of the assistance is to prepare pregnant women in the third trimester to be ready to face physical, psychological, and mental changes when the stomach is getting bigger, and childbirth is about to go through. The method used training with a series of lectures and doing prenatal yoga exercises. Puskesmas Sangkrah of Surakarta City is a partner in community service. The results achieved were a change in knowledge and understanding of third-trimester pregnancy regarding the physiology of the third pregnancy from before being given education. The average knowledge was 72%. After being given health education, the mother's knowledge increased to 100%. After doing prenatal yoga, eleven mothers who participated in yoga stated that the mother was able to accept the changes in the third trimester of pregnancy because she was able to start processing their emotions and enjoying their pregnancy.